Applying scheduling policies to improve qoe in wireless voice-over-ip - Lambrinos, Lambros; Djouvas, Constantinos (My University, 2009)
In the increasingly popular Voice over IP (VoIP) application domain, a well known issue relates to the management of available network bandwidth which is usually constrained by uplink capacities as well as access point limitations in the case of wireless connections. An approach that has long been advocated for controlling the admission of new connections based on bandwidth availability is Call Admission Control (CAC). The number of lines available on an intermediary gateway for interconnecting VoIP calls to the Public Switched Telephone Network (PSTN) is also a finite resource but is in many cases considered for granted. To enhance existing CAC schemes, in this paper we propose a scheme that concentrates on managing the availability of such lines by applying various call scheduling policies. The need for line management is not always apparent but it is crucial in wireless mesh networks, and multi-hop user connectivity in general, where the number of users can vary significantly through time. The aim is to allow fairer access to the lines available; the better management of such lines improves Quality of Experience especially for nomadic users who experience opportunistic and intermittent wireless connectivity.
Keywords: Internet telephony; Switching circuits; Telecommunication systems; Quality control